1999
DOI: 10.1097/00005537-199911000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Experience With Direct Puncture Therapeutic Embolization for Adjunctive and Palliative Management of Head and Neck Hypervascular Neoplasms

Abstract: Our results lend further support to the safety and efficacy of DPTE in the management of hypervascular neoplasms of the head and neck. With our increasing experience, this technique is evolving into a primary therapeutic modality for optimal tumor devascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 7 publications
2
57
1
Order By: Relevance
“…13 A percutaneous approach by using liquid embolic material such as cyanoacrylate glue has been shown to be safe and effective in obliterating the vasculature in a number of different hypervascular head and neck lesions. Chaloupka et al 14 performed percutaneous injection of a cyanoacrylate mixture in 24 cases achieving either total or near-total devascularization in 83% of the cases with no serious complications. Abud et al 15 demonstrated that DPE could be performed in head and neck paragangliomas utilizing modified acrylic glue with a high degree of effectiveness, technical success, and a low rate of complications.…”
Section: Discussionmentioning
confidence: 99%
“…13 A percutaneous approach by using liquid embolic material such as cyanoacrylate glue has been shown to be safe and effective in obliterating the vasculature in a number of different hypervascular head and neck lesions. Chaloupka et al 14 performed percutaneous injection of a cyanoacrylate mixture in 24 cases achieving either total or near-total devascularization in 83% of the cases with no serious complications. Abud et al 15 demonstrated that DPE could be performed in head and neck paragangliomas utilizing modified acrylic glue with a high degree of effectiveness, technical success, and a low rate of complications.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer patients, NBCA is indicated for tumor bleeding [72] and can also be used to achieve a palliative therapeutic effect by improving the tumor response [32,41,142,145,176]. In addition, NBCA has been indicated for arterial redistribution and hepatic arterial catheter fixation during hepatic arterial infusion chemotherapy [68,159,180,181].…”
Section: International Situationmentioning
confidence: 99%
“…Sonography guided or CT guided intratumoral injection of a liquid adhesive like N-butyl-2-cyanoacrylate gives better devascularization compared to transarterial embolization and is a safe and effective method of preoperative embolization [11][12][13][14]. Percutaneous direct embolization provides an easy access to hypervascular tumor with a higher chance of achieving complete devascularization [12,36].…”
Section: Discussionmentioning
confidence: 99%
“…Significant intraoperative blood loss is expected so preoperative transarterial embolization has proved beneficial [9,10]. Percutaneous direct intratumoral embolization can also be done with same efficacy [11][12][13][14]. Supraglottic laryngectomy and lateral pharyngotomy are commonly used approaches for managing these paragangliomas [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%